Melan-A/MART1 analog peptide triggers anti-myeloma T-cells through crossreactivity with HM1.24 - Christensen, Olaf; Lupu, Alaviana; Schmidt, Stefanie; Condomines, Maud; Belle, Sebastian; Maier, Ariane; Hose, Dirk; Neuber, Brigitte; Moos, Marion; Kleist, Christian; Terness, Peter; Ho, Anthony Dick; et al. (Journal of immunotherapy, 2009)
The Melan-Aaa26-35 (EAAGIGILTV) peptide is a human leukocyte antigen (HLA)-A2-restricted T-cell epitope within the Melan-A/MART-1 tumor antigen expressed on malignant melanoma cells. Melan-A and Melan-A analog (ELAGIGILTV, Melan-Aaa26-35*A27L) specific T-cells can be expanded reliably for immunotherapeutic approaches in vitro. We studied the ability of Melan-A analog (ELAGIGILTV, Melan-Aaa26-35*A27L) specific T-cells to recognize the HM1.24aa22−30 (LLLGIGILV) peptide within the HM1.24 antigen presented by normal and malignant plasma cells. Peripheral blood mononuclear cells from HLA-A2+ healthy donors and HLA-A2+ multiple myeloma (MM) patients were stimulated with Melan-A analog peptide-loaded autologous dendritic cells, and expanded in vitro. T-cell activation was assessed by interferon-γ specific enzyme-linked immunosorbent spot and cytotoxicity by 51Chromium-release-assays. The frequency of Melan-A analog specific CD8+ T-cells was detected by using tetramers. Melan-A analog specific T-cells from HLA-A2+ healthy donors and HLA-A2+ MM patients showed a interferon-γ secretion mediated by HM1.24aa22−30 peptide-pulsed T2 cells and lysed the HLA-A2+ HM1.24+ U266 and XG-1 human myeloma derived cell-lines as well as the B-lymphoblastoid cell-line IM-9. Melan-A analog specific T-cells from MM patients specifically lysed autologous MM cells. The current data demonstrate that Melan-A analog specific T-cells crossreact with HM1.24aa22−30. They might be a tool for the future use in immunotherapy against MM.